2020
DOI: 10.1155/2020/5724024
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index (BMI) and Its Influence on the Cardiovascular and Operative Risk Profile in Coronary Artery Bypass Grafting Patients: Impact of Inflammation and Leptin

Abstract: Background. Obesity is related to coronary artery disease (CAD) and worse outcomes in coronary artery bypass graft (CABG) patients. Adipose tissue itself is an endocrine organ that secretes many humoral mediators, such as adipokines, which can induce or reduce inflammation and oxidative stress. Objectives. We investigate the relationship between the body mass index (BMI), inflammation, and oxidative stress by measuring serum levels of leptin, interleukin-6, and 3-nitrotyrosine in CABG patients and correlate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…BMI was directly correlated with several oxidative stress parameters, positively with p47phox expression and hydroethidium oxidation, but negatively correlated with endothelial nitric oxide synthase (eNOS) phosphorylation and dihydrofolate reductase expression in patients undergoing coronary artery bypass graft surgery [34]. In patients with IHD, BMI also correlated with leptin levels and oxidative stress markers, with an impact on cardiovascular and operative risk profiles [35]. The coexistence of hypercholesterolemia and obesity in children caused additive increase of 8-isoprostanes and soluble nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) 2-derived peptide (sNox2-dp, a marker of NOX2 activation) and additive impairment of endothelial function measured by flow-mediated dilation (FMD) [36].…”
Section: Obesity and Redox Signaling In Myocardial Infarctionmentioning
confidence: 98%
“…BMI was directly correlated with several oxidative stress parameters, positively with p47phox expression and hydroethidium oxidation, but negatively correlated with endothelial nitric oxide synthase (eNOS) phosphorylation and dihydrofolate reductase expression in patients undergoing coronary artery bypass graft surgery [34]. In patients with IHD, BMI also correlated with leptin levels and oxidative stress markers, with an impact on cardiovascular and operative risk profiles [35]. The coexistence of hypercholesterolemia and obesity in children caused additive increase of 8-isoprostanes and soluble nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) 2-derived peptide (sNox2-dp, a marker of NOX2 activation) and additive impairment of endothelial function measured by flow-mediated dilation (FMD) [36].…”
Section: Obesity and Redox Signaling In Myocardial Infarctionmentioning
confidence: 98%
“… 92 Withal, adipose tissue itself is an endocrine organ that can secrete a variety of body fluid mediators, such as adipokines, which can induce or reduce inflammation and oxidative stress. 93 Some studies have provided evidence that rodent models have demonstrated that fat inflammation pathways play an important role in diet and obesity-related metabolic disorders, and mRNA microarrays and secretion profiles of human adipose tissue and fat cells have identified similar inflammatory pathways in the obesity Inflammation pathway activated by endotoxin. 94 …”
Section: Dietary Inflammatory Index (Dii)mentioning
confidence: 99%
“…One explanation for this paradox is that patients with higher BMI may have a lower postoperative bleeding volume and transfusion rate; thus, such patients may save blood products during on-pump CABG factor that contributes to higher survival rates (14). On the other hand, sternal wound infections are more prevalent in obese patients and prior studies have shown increased morbidity and mortality rates in obese patients (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%